CONCEPT ENRICHMENT OF BIODIVERSITY USING BUSH DIVERSITY BOOKLET IN MANGROVE AREA, ALUH-ALUH BESAR VILLAGE, BANJAR - Nur Aulia Rahmah; Hardiansyah Hardiansyah; Noorhidayati Noorhidayati (ATRIUM PENDIDIKAN BIOLOGI, 2022)
Mangrove forest area in Aluh-Aluh Besar Village, Banjar District is an area that has local potential such as shrubs diversity. This potency can be used in education sector as environmental-based learning resources for biodiversity material in high school. The purpose of this research is to describe the booklet teaching materials that can be developed about shrubs diversity in Mangrove Area Aluh-Aluh Besar Village, Banjar District. This booklet is arranged as learning resource for exercise material of biodiversity concept in high school. This research used Research and Development (R&D) method with Borg and Gall model that restricted to design revision stage. The result validation of the developed booklet is declared valid from an average validity score of 3.75. The results of the reability response by 5 students acquire 83.6 % results and were categorized as very good.